Late Cenozoic mammal bio-chronostratigraphy in southwestern Buenos Aires Province, Argentina (Ameghiniana, 2013)
Abstract. Fossil land mammals from ten localities of southern Buenos Aires Province, Argentina were studied. A new stratigraphic pattern based on materials with reliable stratigraphic provenance is proposed and compared to that of the central-east of the Pampean region. Correlation of fauna and calibration o the time scale suggest that the interval represented in the study area encompasses from the Late Miocene (Huayquerian Age) to the Present. Six biozones were defined for this lapse: Xenodontomys ellipticus Zone, Plohophorus cuneiformis-Actenomys priscus Zone, Ctenomys kraglievichi Zone, Equus (A.) neogaeus- Macrauchenia patachonica Zone, Ozotoceros bezoarticus Zone, and Bos taurus-Ovis aries Zone. They are correlated within a chronostratigraphic chart.Resumen. BIO-CRONOESTRATIGRAFÍA DE MAMÍFEROS DEL CENOZOICO TARDÍO EN EL SUDOESTE DE LA PROVINCIA DE BUENOS AIRES, ARGENTINA. Se estudiaron diez localidades fosilíferas del sur de la provincia de Buenos Aires, Argentina. Sobre la base de los mamíferos fósiles se elaboró un esquema estratigráfico para el área y se comparó con el patrón del centro-este de la región pampeana. La correlación de la fauna y su calibración con la escala temporal sugieren que el intervalo representado en el área comprende desde el Mioceno Tardío (Edad Huayqueriense) hasta el presente. Se definieron seis biozonas para este lapso: Biozona de Xenodontomys ellipticus, Biozona de Plohophorus cuneiformis-Actenomys priscus, Biozona de Ctenomys kraglievichi, Biozona de Equus (A.) neogaeus-Macrauchenia patachonica, Biozona de Ozotoceros bezoarticus y Biozona de Bos taurus-Ovis aries. Estas biozonas se correlacionan dentro de una carta cronoestratigráfica.